О проблеме учета ионосферной задержки навигационных сигналов в задачах точного ГНСС-позиционирования - Жалило, А. А.; Бессонов, Е. А. (ХНУРЭ, 2011)
The results of researches of the spatial-temporal properties of the differential ionospheric linear combinations in order to achieve centimeter accuracy of positioning using single-frequency GNSS equipment on the baselines over 50 km are presented.
Keywords: ГНСС-приемник; ионосферная задержка